PERCOBAAN FRAKSIONASI-DISTILASI MINYAK TERPENTIN DARI PINUS MERKUSII JUNG ET DE VRIESE - Bambang Wiyono; Toga Silitonga (Jurnal Penelitian Hasil Hutan, 1989)
Turpentine  oil  was optained  from  rosin  factory   in Paninggaran,   Central  Java,  and  Sukun,  East  Java.   Both  samples were  separated   by  fractional  distilation   into  several  fractions.   The  distilling  was conducted   at boiling  temperature   with atmospheric   pressure.   The  boiling point   ranges  were  156  -   164°C  for  the  first  fraction;   164  -   167°C  for  the  second fraction;  167 -  170° C for  the third fraction;  and  170° C and  upward  for the residual fraction.The   results  indicated   that   the  amount   of  turpentine   fractions   from  Paninggaran  and  Sukun   were  consecutively 73.60%   and  70.0%  of  first  fraction:   1340%  and  15.80%   of  second  fraction;  3.17%   and 3.79%  of  third fraction;  and 9.97% and  9.86%  of  the  residual.  Based  on  the  boiling  temperature   of  each  component,    the  first  fraction   is assumed  to contain n-heptane,   p-thujene,    a-pinene,   and  camphene;   β-pinene    and  myrcene   in  the  second   fraction;  myrcene,   β-phellandrene, and  ∆3-carene  in  the  third  fraction;  and  the  residual  fraction   contains,   β-phellandrene. ∆3-carene,   p-cymene,   limonene, ά-and ɤ-terpinene,  etc.   The  major  components    of  turpentine   oil are ά-and β-pinene.   These  components    can  be obtained by  decreasing  the  boiling  range to  154  -   158° C for  ά-pinene   and  164  -   166° C for  β-pinene.  The  fractional   distillation with   these  temperatures   is expected   to  increase  the  utilization   of  turpentine   as raw material  for  synthetic pine  oil,  perfumery,   etc.